Case-control evaluation of the effectiveness of the G1P[8] human rotavirus vaccine during an outbreak of rotavirus G2P[4] infection in central Australia - Snelling, Thomas; Andrews, R.; Kirkwood, C.; Culvenor, S.; Carapetis, J. (Oxford University Press, 2011)
Summary: The human rotavirus vaccine was evaluated during an outbreak of rotavirus G2P[4] infection in central Australia. No overall protective effect against hospitalization was demonstrated, raising concerns over the durability of vaccine protection against heterotypic strains. Background: Two and a half years after commencing routine vaccination with human rotavirus vaccine, an outbreak of rotavirus G2P[4] infection occurred in central Australia. Vaccine effectiveness against a P[8]-containing strain (G9P[8] ) had been demonstrated previously in this setting. This subsequent outbreak provided the opportunity to evaluate vaccine effectiveness against hospitalizations for a non-vaccine-related genotype in the same population. Methods: A case-control study was nested within a cohort of vaccine-eligible children listed on a populationbased immunization register. Children with rotavirus-confirmed gastroenteritis were individually matched by date of birth and Indigenous status with 4 control subjects. Results: Forty-one cases met the inclusion criteria, and 21 were severe cases among infants aged < 12 months. Nineteen (46%) of 41 case patients had received 2 doses of human rotavirus vaccine, compared with 87 (53%) of 164 control subjects. Vaccine effectiveness against rotavirus-related hospitalization was 19% (odds ratio,.81; 95% confidence interval,.32-2.05) for 2 doses compared with none. On secondary analysis, there was evidence of a protective effect against disease complicated by acidosis in the subset of infants aged < 12 months (odds ratio,.15; 95% confidence interval,.03-.84). Conclusions. Evidence was not found for an overall protective effect of human rotavirus vaccine against hospitalization for rotavirus disease in this setting. Post hoc analyses suggested a protective effect against severe disease in young infants. © The Author 2011.